Community Service Project At Smes In Batam: Reviewing Financial Statements and Calculating Corporate Annual Income Tax - Felix Williansyah; Meiliana Meiliana (Universitas Internasional Batam, 2024)
Following the Decree of the Minister of Education and Culture Number 3 of 2020, Universitas Internasional Batam implements the Merdeka Belajar Kampus Merdeka (MBKM) policy. This community service project implemented MBKM policy. A team consisting of a student and a lecturer from the Undergraduate Program in Accounting conducted this project. Team members helped SMEs in Batam reviewed and improved their financial statements and calculated their annual corporate income tax. We implemented this project jointly with PT Anugerah Manajemen Abadi during the period of August to December 2022. PT Anugerah Manajemen Abadi introduced us to four SMEs with limited knowledge and human resources who needed help understanding tax regulations. Those SMEs are engaged in onion trading, machinery, freight forwarding, and housing development. The Team analyzed the financial reports presented by SMEs and adjusted them according to tax regulations (Government Regulation of The Republic of Indonesia Number 7 of 2021 about general provisions and tax procedures). Adjustments were made, among others, to expenses related to